(untitled) (REMUNOM, 2026)
This article aims to critically analyze the multiplicity of epistemologies that underpin the field of educational, institutional, program, and public policy evaluation, understanding it as a specific body of knowledge that is historically constituted and epistemologically plural. It is based on the assumption that evaluation cannot be reduced to a technicist, praxeological, and instrumental procedure; rather, it is configured as a human, scientific, and political act of valuation, permeated by different conceptions of knowledge, science, method, and reality. Methodologically, the study develops a qualitative bibliographic and documentary research design, articulating classical and contemporary contributions from epistemology and the philosophy of science. The quadripolar methodological strategy is explored through its epistemological, theoretical, morphological, and technical poles. The analysis traces the historical trajectory of method from Classical Greece to contemporary times, highlighting Bachelardian epistemology and the multiplicity of forms of knowledge. The study culminates in a comparative analysis of diverse epistemological currents, making explicit their implications for evaluative practice. The expected results point to the need to overcome reductionist, instrumental, or monolithic views of evaluation, recognizing it as a field marked by epistemological disputes in which diverse rationalities and experimentalities coexist. It is concluded that the constitution of evaluative knowledge and the consolidation of a specific epistemology of evaluation require constant epistemological vigilance, openness to complexity, and critical articulation among different epistemological perspectives in order to address the imprecise and dynamic nature of institutional and educational reality.